Morbidity Pattern among the Geriatric Population of the Rural and Urban Areas of Chattogram District in Bangladesh - Hoque, S M Kamrul; Paul, Sujat; Yusuf Chowdhury, Mohammed Abu; Chowdhury, Muhammed Raihan; Kausar, Mohammad Abu (Journal of Chittagong Medical College Teachers’ Association, 2022)
Background: Bangladesh is an “ageing nation” with 9.3% of its population being above 60 years of age, and by 2050 their number will increase to 22% of the total population. Understanding health problems among the elderly is a prerequisite for comprehensive geriatric care. This study aimed to investigate the morbidity pattern and its associated factors among the senior population in a rural and urban area of the Chattogram district of Bangladesh. Materials and methods: Through a multistage sampling, 408 subjects aged 60 years and over from two Upazilas of Chattogram district (n=203) and two wards of Chattogram City Corporation and one Paurosova (n=205) were included in this cross-sectional study from October 2018 to September 2019. Socio-demographic and clinical data were collected through face-to-face interviews, medical record analysis, clinical examination, and investigations. Results: The most common morbidities identified were the visual problem (87.3%), followed by osteoarthritis (53.9%), hypertension (44.3%), anaemia (37.5%) and Diabetes Mellitus (35.6%). Prevalence of hearing loss, dementia, and urinary incontinence were 28.9%, 16.7%, and 15.4%, respectively. The urban elderly had significantly higher proportion of hypertension (49.3% vs. 39.4%), diabetes Mellitus (40.5% vs. 30.5%), and dental problems (26.3% vs. 18.2%) whereas prevalence of anemia (40.4% vs. 24.9%) and COPD (17.6% vs. 10.7%) were more common in rural area. Rural dwellers were more likely to have lower education and wealth than urban dwellers and were more economically dependent on others than urban dwellers. In multivariable-adjusted models, factors associated with chronic conditions and/or multimorbidity were female sex, older age, and low economic condition. Conclusion: The elderly population represents a high prevalence of morbidity with significant rural-urban variations in factors associated with morbidity. Further exploration and understanding of these rural-urban health disparities may help develop better-targeted strategies to improve health care delivery and, consequently, the health condition in rural and urban areas. JCMCTA 2022 ; 33 (2) : 95-99